Spatial Simulation Model of Bauxite Grades Using R Data Analysis: Its Implication for Exploration Activity - Rosmalia Dita Nugraheni; Dedi Sunjaya; Bronto Sutopo; Mohammad Apriniyadi; Cahyaningratri Prima Riyandhani; Imam Setiaji Ronoatmojo (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.In exploration, the investigation of prospective area encounters several barriers of land ownership, budget limitation and exhausting permit procedures. To speed up the exploration activities of bauxite deposits, bauxite characteristics and grades of the gap areas should be simulated based on the available set of test pit data. This study aimed to address the limitations and optimize the exploration boundaries using R. R data analysis weaves the framework of kriging geostatistics that required information from the adjacent data. This study utilizes the geochemical data of Al2O3, Fe2O3, SiO2 and TiO2 from 296 test pit sampling sites to extrapolate the blank data. The geochemical data used for R analysis were taken from bauxite horizon, while the other mineralogical properties were taken entirely from the exposed bedrock and test pit data. To verify the result of R analysis, recent data of the simulated area were used as a comparison. The R result shows the prediction value is slightly below the actual value of Al2O3. The kriging simulation of Al2O3 was correlated with test pit and mineralogical characters of samples and reveals that the predicted value of simulation closely represents the true value of Al2O3 grades. Extrapolation results of Fe2O3 and RSiO2 with regards to Al2O3 grades are suggesting that higher grade of bauxite underwent desilication and deferruginization as evidenced by a high value of Index of Lateritization. It can be inferred that this attempt points out the advantages of a quick and reliable projection of bauxite laterite deposits from the limited parameters.